Pelestarian Kuliner Tradisional Halua Sebagai Simbol Budaya Melayu Pada Gen Z Di Desa Bukit Harapan - Tuty Nadhia Salsabila; Cindy Fadilah; Kinanty Siti Hardian; Sulaswati Waddunia; Dinda Auliah Rahmah (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
Preserving traditional culinary traditions is an important part of preserving local cultural heritage amidst the currents of globalization that influence the consumption patterns of the younger generation. This study aims to analyze the role of traditional Halua cuisine in maintaining Malay cultural identity among Generation Z in Bukit Harapan Village. The research method used was descriptive qualitative, with data collection techniques through observation, in-depth interviews, and literature review. The results indicate that Halua serves not only as a traditional food in community activities but also as a cultural symbol that enhances Generation Z's sense of pride and attachment to traditional values. Active participation by Gen Z through digital media and local cultural activities has proven to be a crucial strategy in preserving this cuisine. These findings suggest the need for an intergenerational approach and the integration of digital technology to ensure the sustainability of Halua preservation in the future.